Tecnopedagogía en la formación profesional de los estudiantes de las carreras pedagógicas de la Universidad Nacional de Loja. - Santos Vásquez, Cecibel del Cisne (2024)
The integration of Information and Communication Technologies (ICT) in current education has succeeded in expanding teaching and learning environments through the use of various technological resources to enhance the educational process. Therefore, a technopedagogical methodology is currently proposed for the development of these methods. Among the project objectives, there is an intention to determine, through an exploratory study, the impact of technopedagogy on the professional training of students in pedagogical careers at the Universidad Nacional de Loja, analyzing and identifying the resources and their contribution to such training. Hence, the methodological process followed involves collecting the opinions of university students through the application of a questionnaire focused on analysis and identification. Based on the results, the goal is to determine which technopedagogical resources are used and their contribution to professional training. As a result, the main technopedagogical resources used in the professional training of university students have been identified, including platforms, tools, and educational applications. The significant contribution of technopedagogy in the professional training process lies in developing skills and abilities aligned with education in the innovative world we inhabit. This research is exploratory, descriptive, and statistical, employing a scientific, analytical, descriptive, and statistical method. Conclusions and recommendations have been established, focusing on the use of technology in professional training to contribute to the motivation, evaluation, and control of educational processes. Keywords: ICT; innovation; pedagogy; professional training; education.